Perception of mothers regarding the importance of child immunization - Leiliane Bezerra Santos; Cristina Costa Melquíades Barreto; Francisca Lívia Sepúlveda Silva; Kamila Cristiane de Oliveira Silva (Rev Rene)
Immunization is one of the most important measures in the prevention of preventable infectious diseases. It is an exploratory descriptive research, with qualitative approach, carried out in a Family Health Unit (FHU) in the state of Paraiba, Brazil, which aimed to know the perception of mothers about the importance of child immunization. The sample consisted of thirty mothers who were enrolled at the FHU and with children aged zero to twelve years. Data collection occurred in September 2008 and a semi-structured questionnaire was used. The results revealed that most mothers believe in the vaccination process and know the importance of immunization as a means of prevention of diseases.